Local Wisdom of Pest Attack Control in Residential Areas (Study Case: Gunung Meja Nature Park, West Papua, Indonesia) - Karubuy, Claudia Novia Sandy; Siburian, Rima; Murdjoko, Agustinus (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Healthy plants can be seen from good morphology and are not even attacked by pests. Local community knowledge of seeing symptoms and signs of plant stature will be very helpful, especially in dealing with problems related to plant growth. This study aims to determine the form of local wisdom in dealing with plant pests in residential areas around the Gunung Meja Nature Park. The method used is observation and interviews related to the identification of forms of attack, the level of pest attack on plants, and their handling by the community. The research object is focused on multipurpose tree species that produce wood and non-timber trees such as fruits that have high economic value. The results showed that the number of plant species in Anggori was 137 plants with a diversity index (H) of 2.956 which was included in the medium category. Plants in Anggori also suffered damage caused by pests with an attack frequency (FS) of 50% and attack intensity (IS) on plants of 21%. Pest control has been carried out by the community traditionally, such as 12% pruning, 8% logging, 20% fumigation, 8% stove ash and 16% soap to eradicate pest attacks.